The Characterization of Bamboo-Derived Cellulose Via Combined Pretreatment and Dissolution Effect in Ionic Liquid - Loi, Xue Min (Progress in Engineering Application and Technology, 2023)
Recently, ionic liquid (ILs) as a green solvent has replaced the use of volatile organic solvent in the dissolution of cellulose for bio-based fabrics. This study aims to characterize the bamboo-derived cellulose and dissolution effects of cellulose in two types of ionic liquids; 1-allyl-3-methyl-imidazolium-chloride, [AMIM]Cl and 1-butyl-3-methyl-imidazolium chloride, [BMIM]Cl prior formation of regenerated cellulose film. The film was synthesized using cellulose extracted from bamboo, Schizostachyum grande via a combination of mechanical and chemical pre-treatment. The extracted bamboo was characterized using particle size analyser (PSA), Fourier-transform infrared spectroscopy (FTIR), X-ray Diffraction (XRD), Differential Scanning Calorimetry (DSC) and Thermal Gravimetric Analysis (TGA). Comparisons were made between the extracted bamboo with raw bamboo fiber and commercial microcrystalline cellulose (MCC). The extracted cellulose was confirmed by removal of lignin. The disappearance of FTIR spectra at 1722 cm−1 and 1602.8 cm-1 which correspond to the C=O stretching frequency of ester group and the stretching vibration of aromatic rings, respectively indicates the removal of lignin. The XRD results showed a significant reduction of crystallinity index (CrI %) in RBF as compared to bamboo cellulose (BC) due to removal of amorphous regions during the chemical treatment. The DSC analysis further confirmed the reduction of crystalline regions in cellulose extracted from bamboo. Similarly, the dissolution and regeneration process reduced the crystallinity of cellulose. However, the dissolution in ionic liquids failed to form a film. Overall, it can be concluded that the absence of co-solvent, inefficient heating approach as well as the degradation of cellulose during dissolution possibly act as contribution factors upon the observed results.